Wirkungen der Investitionsförderung in Ostdeutschland - Joachim Ragnitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
– Investment in East Germany is heavily subsidized. Econometric estimates based on a treatment approach show that the level of investment is significantly higher in firms being supported by state aid. Nevertheless, capital productivity is lower in East Germany, indicating a misallocation of capital. Additionally, there are negative effects in West Germany due to negative crowding-out effects. Therefore state aid in East Germany should be reduced in the medium run.
urn:nbn:de:gbv:3:2-20930
Keywords: O52; R11; R38; R58; 330; Investitionspolitik; Wirkungsanalyse; Neue Bundesländer